Living with Art / Third Edition - Gilbert Rita (Mcgraw Hill Book Company, 1992)
Introduction, Living with Art, What is Art, Themes and Purpose of Art, The Vocabulary of Art, The Visual Elements, Principles of Design, Two-Dimensional Media, Drawing, Painting, Prints, The Camera Arts: Photography and Film and Video, Graphic Design, Three-Dimensional Media, Sculpture, Crafts, Architecture, Environmental Design, Arts in Time, The Ancient World to the Middle Ages, Renaissance to Revolution, The Modern World, Keeping the Art We Live With: Conservation and Restoration, Glossary, Index, Maps.
Introduction, Living with Art, What is Art, Themes and Purpose of Art, The Vocabulary of Art, The Visual Elements, Principles of Design, Two-Dimensional Media, Drawing, Painting, Prints, The Camera Arts: Photography and Film and Video, Graphic Design, Three-Dimensional Media, Sculpture, Crafts, Architecture, Environmental Design, Arts in Time, The Ancient World to the Middle Ages, Renaissance to Revolution, The Modern World, Keeping the Art We Live With: Conservation and Restoration, Glossary, Index, Maps.